1989
DOI: 10.1136/pgmj.65.759.16
|View full text |Cite
|
Sign up to set email alerts
|

How do we know who has had deep vein thrombosis?

Abstract: Summary:An attempt was made to identify all patients diagnosed as having deep vein thrombosis (DVT) in a large teaching hospital during one year. A review of the radiology records showed that 124 (81%) of the 154 venograms performed were for suspected DVT, and that the diagnosis was confirmed in 57 (46%). During the same period, the Hospital Activity Analysis (HAA) records revealed 174 episodes classified as 'phlebitis or thrombophlebitis' in 162 patients. Only 37 of these episodes (21%) had been confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The accuracy of clinical diagnosis of DVT was only 17/35 (50%) and similiar to those reported else where (4,5,6,7). Screening for DVT has shown that up to 65% of proximal DVT is asymptomatic and the diagnosis would not even be considered (14).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The accuracy of clinical diagnosis of DVT was only 17/35 (50%) and similiar to those reported else where (4,5,6,7). Screening for DVT has shown that up to 65% of proximal DVT is asymptomatic and the diagnosis would not even be considered (14).…”
Section: Discussionsupporting
confidence: 76%
“…These drugs with their potential for serious haemorrhagic complications cannot be started or continued for long periods without an accurate diagnosis. Clinical diagnosis of DVT is unreliable (4,5,6,7) and therefore an objective test for accu rate assessment becomes necessary. Contrast venography is recognized as the gold standard examination.…”
Section: Introductionmentioning
confidence: 99%